Optimization of Shallot Growth and Production through Cow Manure Application and Eco Farming: Allium ascalonicum L. - Efbertias Sitorus; Pantas Simanjutak; Lince Romauli Panataria; Meylin Kristina Saragih; Rio Adesta Hutauruk (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
This study aims to determine the effect of cow manure and liquid organic fertilizer eco farming on the growth and production of shallots (Allium ascalonicum L.). This research method uses a Factorial Randomized Block Design (RAK) consisting of 2 factors. The first factor is cow manure (P) consisting of 4 treatment levels, namely: P0 = Control (Without Compost), P1 = 0.5 kg/plot (5 tons/ha), P2 = 1.0 kg/plot (10 tons/ha) and P3 = 1.5 kg/plot (15 tons/ha). The second factor: Eco Farming consists of 3 treatment levels: C1 = 150 ml/plot, C2 = 250 ml/plot, and C3 = 350 ml/plot. The study's results showed that the provision of cow manure significantly affected plant height, number of leaves, wet weight of tubers per sample, and wet weight of tubers per plot. Providing eco farming impacts plant height, number of leaves, dry weight of tubers per sample, and wet weight of tubers per plot. The interaction between cow manure and eco farming had no significant effect on plant height, number of leaves, dry weight of tubers per sample, and wet weight of tubers per plot.